Breaking the DNA-vaccine bottleneck - Danquah, Michael; Forde, G. (IChemE, 2011)
Monash University in Australia has developed a new approach towards DNA vaccine development that has the potential to cut the time it takes to produce a vaccine from up to nine months to four weeks or less. The university has designed and filed a patent on a commercially viable, single-stage technology for manufacturing DNA molecules. The technology was used to produce malaria and measles DNA vaccines, which were tested to be homogeneous supercoiled DNA, free from RNA and protein contaminations and meeting FDA regulatory standards for DNA vaccines. The technique is based on customized, smart, polymeric, monolithic adsorbents that can purify DNA very rapidly. The design criteria of solid-phase adsorbent include rapid adsorption and desorption kinetics, physical composition, and adequate selectivity , capacity and recovery. The new show technology significantly improved binding capacities, higher recovery, drastically reduced use of buffers and processing time, less clogging, and higher yields of DNA.